Some features of Porbandar cyclone of October 1975 - MUKHERJEE , A. K.; SUBRAMANIAN, S. K. (MAUSAM, 1977)
A severe cyclonic storm crossed Gujarat coast near Porbandar on the afternoon of 22 October 1975. This caused large scale damage in the northern parts of Gujarat State. A detailed study on different aspects revealed many features associated with this cyclone, viz. possibility of a cycloidal motion in the trajectory of the storm centre, moisture release in the eastern sectors etc. Evaluation of different types or observation like the satellite pictures, cyclone warning radar observation, post flight reports etc have also been discussed.